The long March: A reform agenda for Latin America and the Caribbean in the next decade / Shahid Jave Burki and Guillermo E. Perry - Burki, Shahid Javed. Perry, Guillermo E. (Washington (State) : The world bank, 1997)
Trata de A reform agenda for Latin America and the Caribbean in the next decade .
1. The financial sector 2. The external sector
incluye índice
Col. Soc
Keywords: 1. INTERGOVERMENTAL FISCAL RELATIONS 2. RECENT EXPERIENCES IN THE REGION